PENDIDIKAN AGAMA ISLAM (PAI) DALAM PENANGGULANGAN RADIKALISME - Ulfa, Ulfa (At-Tuhfah : Jurnal Studi Keislaman, 2018)
Indonesia is a plural and heterogeneous country, and has the potential for multi-ethnic, cultural, multi-religious wealth, all of which are the potential to build a large multicultural country, any religion has a tendency to carry out truth claims because religion is a belief value that must be held firmly by its adherents, the attitude of the truth claim will be positive if it is only intrinsic Orientation in its appreciation and application, not for extrinsic orientation that causes negative prejudice and conflict. Intrinsic religion fulfills all life with motivation and meaning, while extrinsic religion makes religion enslaved to support and justify personal interests, The aim of Islamic education is to form perfect human being.. then Islamic religious education is the solution to make followers of religion not included in the radical, by giving Learning and methods of Non-Radicalism Islamic Education,